SnO2-F Based Electrode Material for Synthesis of Sodium Hypochlorite Solutions - Piletska, Anastasija; Girenko, Dmitry (Видавництво Львівської політехніки, 2013)
Kinetics of galvanostatic formation of hypochlorite-ions on the Pt and FTO surface can indicate the similar character, surface concentration, and the energy of adsorbed radical-type particles. FTO coating shows high electrocatalytic activity towards the synthesis of sodium hypochlorite during the electrolysis of dilute NaCl solutions.
Keywords: sodium hypochlorite; electrolysis; FTO